Long COVID: Clinical characteristics, proposed pathogenesis and potential therapeutic targets - Kenny, Grace; Townsend, Liam; Savinelli, Stefano; Mallon, Patrick W. G. (Frontiers in Molecular Biosciences, 2023)
The emergence of persistent ill-health in the aftermath of SARS-CoV-2 infection has presented significant challenges to patients, healthcare workers and researchers. Termed long COVID, or post-acute sequelae of COVID-19 (PASC), the symptoms of this condition are highly variable and span multiple body systems. The underlying pathophysiology remains poorly understood, with no therapeutic agents proven to be effective. This narrative review describes predominant clinical features and phenotypes of long COVID alongside the data supporting potential pathogenesis of these phenotypes including ongoing immune dysregulation, viral persistence, endotheliopathy, gastrointestinal microbiome disturbance, autoimmunity, and dysautonomia. Finally, we describe current potential therapies under investigation, as well as future potential therapeutic options based on the proposed pathogenesis research.